2005
DOI: 10.1021/om0490379
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Molecular Structures of Neutral Nickel Complexes. Catalytic Activity of (Benzamidinato)(acetylacetonato)nickel for the Addition Polymerization of Norbornene, the Oligomerization of Ethylene, and the Dimerization of Propylene

Abstract: The new neutral nickel complexes PhC(NSiMe 3 ) 2 Ni(acac) (3), PhC(NSiMe 3 ) 2 Ni(acac)-(TMEDA) (4), [PhC(NSiMe 3 ) 2 ] 2 Ni 2 (5), [PhC(NSiMe 3 ) 2 ] 2 Ni‚Li 2 Br 2 (TMEDA) 2 ( 6), (TMEDA) 2 Ni (7), p-MePhC(NSiMe 3 ) 2 Ni(acac) (8), p-MePhC(NSiMe 3 ) 2 Ni(acac)(TMEDA) (9), [p-MePhC-(NSiMe 3 ) 2 ] 2 Ni (10), NiMe 2 Py 2 (11) and [p-MePhC(NSiMe 3 )] 2 Ni(Py) ( 14) have been synthesized and characterized. The solid-state molecular structures of all complexes have been confirmed by low-temperature X-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
51
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 94 publications
6
51
1
Order By: Relevance
“…Precatalyst Ni-1 could be activated with MAO to show moderate activities around 10 5 g PNB /mol Pd h depending on the reaction conditions [130]. Two different catalyst activation processes were tested.…”
Section: Nn-chelate and Bis(n) Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Precatalyst Ni-1 could be activated with MAO to show moderate activities around 10 5 g PNB /mol Pd h depending on the reaction conditions [130]. Two different catalyst activation processes were tested.…”
Section: Nn-chelate and Bis(n) Ligandsmentioning
confidence: 99%
“…In the first procedure, the precatalyst and MAO were mixed, generating the active species before the addition of norbornene. In the second procedure the active sites were generated by the activation of complex Ni-1 in the presence of the monomer with the first procedure giving higher activities [130]. Furthermore, it was shown that the activities increased with a rising Al/Ni ratio up to 500 and then decreased again.…”
Section: Nn-chelate and Bis(n) Ligandsmentioning
confidence: 99%
“…In recent years there has been increasing interest in the development of late transition metal catalysts for olefin polymerization [1][2][3][4][5][6] due to their application in preparation of high molecular weight polyethylene (PE) and toleration of polar solvents, even polar monomers [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Zirconocene and titanocene complexes have proven to be efficient for the vinyl polymerization of norbornene. [11][12][13][14][15][16] Many late transition metal catalysts based on cobalt, [17,18] nickel, [19][20][21][22][23][24][25][26][27] or palladium [28][29][30][31][32][33] have also been used successfully.…”
Section: Introductionmentioning
confidence: 99%